Leveraging AI for Enhanced Security: A Technical Perspective - Deepak Bhaskaran, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative impact of artificial intelligence on modern cybersecurity operations. The article examines how AI-driven systems have revolutionized threat detection, anomaly identification, and incident response capabilities while significantly improving operational efficiency in security operations centers. The article investigates advanced applications of quantum-enhanced pattern recognition, regulatory compliance automation, and automated incident response systems. Through detailed analysis of enterprise implementations, this article demonstrates how AI integration has enhanced security posture while reducing operational overhead. This article also addresses critical implementation considerations, including infrastructure requirements, data quality demands, and ethical implications of automated security decisions. This article provides insights into the practical challenges and strategic benefits of implementing AI-driven security solutions in enterprise environments.
Keywords: Quantum-Enhanced Cybersecurity; AI-Driven Threat Detection; Automated Incident Response; Regulatory Compliance Automation; Pattern Recognition Systems